Lactoferrin Induces Osteoblast Growth through IGF-1R - Jian-Ming Hou; En-Yu Chen; Fan Lin; Qing-Ming Lin; Ying Xue; Xu-Hua Lan; Man Wu (International Journal of Endocrinology)
Objectives. To investigate the role of the IGF-1R by which lactoferrin induces osteoblast growth. Methods. Osteoblast received 5 d lactoferrin intervention at a concentration of 0.1, 1, 10, 100, and 1000 μg/mL, and the IGF-1 and IGF-1R were detected using RT-PCR and western blot. The osteoblast into the control, 100 μg/mL lactoferrin, Neo-scramble (NS, empty vector), NS + 100 μg/mL lactoferrin, shIGF-1R and shIGF-1R + 100 μg/mL lactoferrin group. We test the apoptosis and proliferation and the level of PI3K and RAS in osteoblasts after 5 d intervention. Results. (1) 1, 10, 100, and 1000 μg/mL lactoferrin induced the expression of IGF-1 mRNA and protein. 10 μg/mL and 100 μg/mL lactoferrin induced the expression of IGF-1R mRNA and protein. (2) Lactoferrin (100 μg/mL) induced osteoblast proliferation while inhibiting apoptosis. Osteoblasts with silenced IGF-1R exhibited decreased proliferation but increased apoptosis. MMT staining and flow cytometry both indicated that there was no significant difference between the shIGF-1R group and the shIGF-1R + 100 μg/mL lactoferrin group. (3) Lactoferrin (100 μg/mL) induced PI3K and RAS phosphorylation and silence of IGF-1R resulted in decreased p-PI3K and p-RAS expression. Lactoferrin-treated shIGF-1R cells showed significantly higher level of p-PI3K and p-RAS when compared with shIGF-1R. Conclusion. Lactoferrin induced IGF-1/IGF-1R in a concentration-dependent manner. Lactoferrin promoted osteoblast proliferation while inhibiting apoptosis through IGF-1R. Lactoferrin activated PI3K and RAS phosphorylation via an IGF-1R independent pathway.